Akt1 genetic variants confer increased susceptibility to thyroid cancer. Issue 11 (November 2020) - Crezee, Thomas; Petrulea, Mirela; Piciu, Doina; Jaeger, Martin; Smit, Jan W A; Plantinga, Theo S; Georgescu, Carmen E; Netea-Maier, Romana
Abstract : The PI3K-Akt-mTOR pathway plays a central role in the development of non-medullary thyroid carcinoma (NMTC). Although somatic mutations have been identified in these genes in NMTC patients, the role of germline variants has not been investigated. Here, we selected frequently occurring genetic variants in AKT1, AKT2, AKT3, PIK3CA and MTOR and have assessed their effect on NMTC susceptibility, progression and clinical outcome in a Dutch discovery cohort (154 patients, 188 controls) and a Romanian validation cohort (159 patients, 260 controls). Significant associations with NMTC susceptibility were observed for AKT1 polymorphisms rs3803304, rs2494732 and rs2498804 in the Dutch discovery cohort, of which the AKT1 rs3803304 association was confirmed in the Romanian validation cohort. No associations were observed between PI3K-Akt-mTOR polymorphisms and clinical parameters including histology, TNM staging, treatment response and clinical outcome. Functionally, cells bearing the associated AKT1 rs3803304 risk allele exhibit increased levels of phosphorylated Akt protein, potentially leading to elevated signaling activity of the oncogenic Akt pathway. All together, germline encoded polymorphisms in the PI3K-Akt-mTOR pathway could represent important risk factors in development of NMTC.